Between Country and City: Construction of Identity in the Autobiographic Narratives of the Post-War Vilnius Inhabitants - Būgienė, Lina (Tautosakos darbai, 2018)
The basis of the article comprises oral interviews collected in the course of fieldwork carried out for the project „Plots of Individual Modernization in the Autobiographic Narratives of the First Generation Urban Inhabitants (Post-War Period in Vilnius)” and other sources, including published memoirs, essays, and various documents. The main question is, in what way, when and to what extent (if at all) did people arriving to Vilnius during two post-war decades adapt there, becoming (perceiving themselves as) the urban dwellers? To answer that question, the author applies the oral history approach, while using narrative analysis currently particularly favored by folklore researchers for more detailed examination of oral autobiographic narratives. She pays attention to some distinctive features of narrative contents and form that allow for deeper insight into the structure of narrative and reconstruction of the essential components of the narrator’s self-identity. The article starts with survey of the historical, social, ideological and demographic shifts taking place in Vilnius during the WWII and in the course of the post-war period. During this time, Vilnius experienced such immense cataclysms that seemed rather exceptional even in the context of that dramatic historical period, with over 90 per cent of its former inhabitants either killed or exiled, and huge part of the city becoming ruins. Having changed also its political system and national affiliation, the devastated city gradually filled in with new population. The new arrivals mostly came from countryside or small townships, bringing along their typical everyday routines, tactics of procuring the necessary living means, and ways of communication. In the first post-war decade, marked by massive devastation, shortages and lack of supplies, interpersonal relations and mutual assistance were of utmost importance: people formed “country-like” neighborhoods in the city, helping and supporting each other almost as family members. Some of them even engaged in agricultural practices (growing vegetables in the yards of the city center, etc.). According to their narratives, at that time they did not care so much for the city’s history, culture, and identity, even for the enforced socialist ideology, concentrating instead on daily survival. The situation altered significantly from the end of the 1950s, after the Stalin’s death, and with relative economic growth starting to yield its results. The government launched an extensive housing program, with entire new living areas of residential blocks springing up in a rather short time. Many families were able to acquire new modern flats and upgrade their living conditions. However, as is evident from the memoirs, this also involved growing alienation and breaking of the formerly established social ties. The city experienced a demographic boom, with Lithuanians making the majority of its population – for the first time in its history. Many of the new inhabitants were young people coming either to study at the University or at a number of the newly opened institutes (the result of the expanded modern system of education), or seeking work at the new factories. These people seem to have been much more inclined to reflect upon the history and culture of Vilnius, its symbolic significance as the Lithuanian capital, and its urban identity. However, even they preserved some of their inherited rustic practices and preferences in taste and ways of living, creating some kind of peculiar “folk-urban” identity of the Vilnius’ dwellers. Thus, the nowadays Vilnius has some characteristic features of the urban dynamics and patterns of everyday life that seem to be rather unique and call for thorough investigation in terms of urban anthropology.